Hydraulic fracture network propagation in a naturally fractured shale reservoir based on the "well factory" model. (January 2023) - Zhang, Haoyu; Chen, Junbin; Zhao, Zhengyan; Qiang, Jianli
Abstract: In different geological and engineering conditions, it is important to study the stress interference of multiple fractures and interaction of natural fractures in "well factory" fracturing to improve the complexity of fracture networks. For this purpose, a 2D, coupled stress-seepage-damage field cohesive model with random propagation of hydraulic fracture was developed, and a random function was used to simulate the natural fractures distribution in a real reservoir. Orthogonal test was designed to investigate the geological and engineering parameters impacting the evolution of zipper fracturing and modified zipper fracture networks. The results show that in naturally fractured reservoirs, hydraulic fracture can open natural fractures and promote the formation of complex fracture networks by combined, induced manner. Higher stress differences lead to simpler fracture networks and straighter hydraulic fracture propagation paths; When pre-existing natural fracture is longer, the propagation direction of hydraulic fracture is more likely to be paralleled with natural fracture; However, the stress shadow effect of multiple fractures may potentially lead to failure of some hydraulic fracture initiation. In addition, the fracture initiation sequence of multiple fractures has a significant effect on the evolution of the fracture networks. The results of the study have important significance for parameter optimization of well factory fracturing in naturally fractured reservoirs.